2011
DOI: 10.1089/apc.2010.0371
|View full text |Cite
|
Sign up to set email alerts
|

Bisexual Behavior and Infection with HIV and Syphilis Among Men Who Have Sex with Men Along the East Coast of China

Abstract: This study examined the correlates of bisexual behavior and infection with HIV/syphilis among men who have sex with men only (MSM-only) and those who have sex with both men and women (MSMW) in Shandong, China. Cross-sectional surveys probed sociodemographic information, sexual and drug use behaviors, knowledge, and use of prevention services; blood samples were tested for HIV/syphilis status. Of 2996 participants, 39.5% acknowledged being MSMW; 60.5% being MSM-only; 2.5% were HIV-infected with similar rates fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 45 publications
(78 reference statements)
3
39
0
Order By: Relevance
“…Our other study among Shandong MSM found that bisexual men are more likely to be older and have lower levels of HIV-related knowledge than men who have sex with men-only. (Liao, Kang, & Jia, 2011) The common bisexual practice showed in the present study were consistent with our previous study and other reports in China (Choi, Gibson, Han, & Guo, 2004; Gu, Qu, Lu, Luo, Wang, & Gu, 2004; Jiang, Cao, Zhang, Xia, Gong, Xue et al, 2006; Liao et al, 2011; X. Ma et al, 2007b; Ruan, Yang, Zhu, Ma, Li, Zhao et al, 2008), it is more common than a corresponding figure obtained in the West (Hightow, Leone, Macdonald, McCoy, Sampson, & Kaplan, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Our other study among Shandong MSM found that bisexual men are more likely to be older and have lower levels of HIV-related knowledge than men who have sex with men-only. (Liao, Kang, & Jia, 2011) The common bisexual practice showed in the present study were consistent with our previous study and other reports in China (Choi, Gibson, Han, & Guo, 2004; Gu, Qu, Lu, Luo, Wang, & Gu, 2004; Jiang, Cao, Zhang, Xia, Gong, Xue et al, 2006; Liao et al, 2011; X. Ma et al, 2007b; Ruan, Yang, Zhu, Ma, Li, Zhao et al, 2008), it is more common than a corresponding figure obtained in the West (Hightow, Leone, Macdonald, McCoy, Sampson, & Kaplan, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, enrolled subjects may visit other clinics for STD treatments, lowering the estimated STD incidence. Nevertheless, the STD rate reported here is similar to that reported in previous studies, 12,14,15,21,24,25,42,43 and represents the current scenario in Taiwan.…”
Section: Discussionsupporting
confidence: 90%
“…Fan and associates 24 reported that HIV infection was associated with syphilis among MSM in Beijing, China, and that syphilis control strategies such as changing social norms about condom use may have an impact on HIV prevention. 24 Liao and colleagues 25 noted that targeting the highly prevalent bisexual behavior with multiple sexual partners and unprotected sex in Shandong's gay community may have an influence on HIV transmission. 25 Ko and associates 21 also highlighted that 1 year after enrollment into the CM program in Tainan, Taiwan, 80% of the HIVpositive patients practiced safe sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSM/TW play a bridging role in the transmission of HIV and other STIs to sexual networks in which the majority is heterosexual 10 11. Several studies have shown significantly higher rates of sexual risk behaviours and syphilis infection among MSM 12–14…”
Section: Introductionmentioning
confidence: 99%